Tegafur–Uracil Maintenance Therapy in Non-Metastatic Head and Neck Cancer: An Exploratory Systematic Review - Hsu-Lin Lee; Po-Huang Chen; Tzu-Chuan Huang; Ren-Hua Ye; Yueng-Hsiang Chu; Jih-Chin Lee; Hong-Jie Jhou; Jia-Hong Chen (Current Oncology)
Background: Tegafur–uracil (UFT), an oral fluoropyrimidine developed in Asia, has been investigated as a maintenance or adjuvant therapy in various malignancies. Its use in head and neck cancers, however, remains limited to small retrospective studies, primarily from East Asia. Given the need for cost-effective maintenance strategies in resource-limited settings, we conducted an exploratory systematic review to evaluate the clinical utility of UFT in non-metastatic head and neck squamous cell carcinoma (HNSCC) and nasopharyngeal carcinoma (NPC). Methods: We systematically searched PubMed, EMBASE, and Cochrane Library from inception through 1 May 2025 for retrospective cohort studies evaluating UFT after definitive therapy in non-metastatic HNSCC or NPC. Study selection followed PRISMA guidelines. Given the heterogeneity of included studies, we performed a structured narrative synthesis using the SWiM (Synthesis Without Meta-analysis) framework to summarize survival outcomes, treatment settings, and clinical contexts. Results: Seven retrospective studies (four HNSCC, three NPC) involving 508 patients were included. UFT was generally administered at 300–400 mg/day for 6–12 months. Across studies, UFT use was associated with favorable disease-free and overall survival trends in high-risk subgroups, including patients with extranodal extension and persistent EBV DNA. Treatment adherence and toxicity profiles were acceptable. Conclusions: While the evidence remains limited and heterogeneous, this review highlights recurring signals of benefit associated with UFT maintenance therapy in selected high-risk patients. Prospective trials are warranted to confirm these findings and better define a possible role of UFT in maintenance therapy in some advanced non-metastatic HNSCC and NPC.